High sustained efficacy of a prophylactic quadrivalent human papillomavirus types 6/11/16/18 L1 virus-like particle vaccine through 5 years of follow-up - Villa, L L; Costa, R L R; Petta, C A; Andrade, R P; Paavonen, J; Iversen, O-E; Olsson, S-E; Høye, J; Steinwall, M; Riis-Johannessen, G; Andersson-Ellstrom, A; Elfgren, K; et al. (British journal of cancer, 2006)
Human papillomavirus (HPV) causes cervical, vulvar, and vaginal cancers, precancerous dysplasia, and genital warts. We report data for the longest efficacy evaluation to date of a prophylactic HPV vaccine. In total, 552 women (16–23 years) were enrolled in a randomised, placebo-controlled study of a quadrivalent HPV 6/11/16/18 L1 virus-like-particle vaccine with vaccination at months 0, 2, and 6. At regular intervals through 3 years, subjects underwent gynaecologic examination, cervicovaginal sampling for HPV DNA, serum anti-HPV testing, and Pap testing, with follow-up biopsy as indicated. A subset of 241 subjects underwent two further years of follow-up. At 5 years post enrolment, the combined incidence of HPV 6/11/16/18-related persistent infection or disease was reduced in vaccine-recipients by 96% (two cases vaccine versus 46 placebo). There were no cases of HPV 6/11/16/18-related precancerous cervical dysplasia or genital warts in vaccine recipients, and six cases in placebo recipients (efficacy=100%; 95% CI:12–100%). Through 5 years, vaccine-induced anti-HPV geometric mean titres remained at or above those following natural infection. In conclusion, a prophylactic quadrivalent HPV vaccine was effective through 5 years for prevention of persistent infection and disease caused by HPV 6/11/16/18. This duration supports vaccination of adolescents and young adults, which is expected to greatly reduce the burden of cervical and genital cancers, precancerous dysplasia, and genital warts.